The Use of CT-Scanning Technology in Wood Value-Chain Research and in Wood Industry : A State of The Art - Fredriksson, Magnus; Broman, Olof; Sandberg, Dick (Luleå tekniska universitet, Träteknik, 2017)
X-ray computed tomography (CT) is a powerful tool for the non-destructive measurement of dynamic processes in wood. After more than 25 years of research at Luleå University of Technology in the field of CT-scanning of wood material, the first industrial CT-scanners are now installed in sawmill production for the in-situ measurement of internal log features to steer of the sawmill process with the help of this information.This paper provides an overview of the potential of CT-scanning in wood-material research and how this data can be used for the modelling and simulation of the wood value chain. A database of CT-images of trees is used to create a log model including the outer shape of the logs and their internal knot structure. Simulation software is used to saw these virtual logs in different positions relative to the sawblade, and also for the crosscutting of the sawn timber to components. The output is dimensions and grades of sawn timber, volume yield as well as an economic result based on real economic conditions. A specially designed climate chamber for CT studies of the drying of sawn timber is used to increase the knowledge of how the drying affects the response from the sawn timber during seasoning. 2018-01-23 (rokbeg);Konferensartikel i tidskrift